Identification of rye chromosomes by flow cytogenetics - Alkhimova, O.G.; Zimina, O.V. (Вiopolymers and Cell, 2017)
The karyotype of the cultivated rye (Secale cereale) is one of the complex plant genomes whose chromosomes are difficult to discriminate because of their similar size. Aim. The purpose of this study is to reveal the chromosome variable sites using DNA repetitive sequences as probes and to define a possibility of sorting rye chromosomes. Methods. Flow cytometry analysis and karyotyping, chromosome sorting, fluorescence in situ hybridization and microscopy. Results. Different distribution of repetitive DNA sites between two rye accessions was demonstrated and an ability to sort chromosome 1 in the ‘Zhyttedaine’ rye variety was shown. This is the second case when chromosome 1R was sorted by flow cytometry in S. cereale. Conclusions. The present study revealed chromosome polymorphisms of microsatellite sequence GAA in accessions and the potential of chromosome sorting in S. cereale varieties. We also identified sequence elements including microsatellites and classic satellites which can be utilized for future research and in rye breeding. Каріотип жита посівного (Secale cereale) розглядається як один із складних рослинних геномів, хромосоми якого важко відрізнити через однаковий розмір хромосом. Мета. Виявлення варіабельних ділянок хромосом з викорис-танням повторюваних послідовностей ДНК в якості зондів і визначення можливості сортування хромосом у сортів жита. Методи. Проточна цитометрія і каріотипування, сортинг хромосом, флуоресцентна гібридизація in situ та мікроскопія. Результа-ти. Показано різний розподіл повторюваних послідовностей ДНК між двома сортами жита і здатність до сортингу хромосоми 1 у жита ‘Життєдайне’. Вдруге продемонстровано можливість сортувати хромо-сому 1R методом проточної цитометрії у жита S. cereale. Висновки. Дослідження виявило хромосомний полімор-фізм микросателітної послідовності GAA у сортів жита і потенційну можливість сортингу хромосом у Secale, і показало, що мікросателіти і класичні сателіти можуть бути використані у подальших дослідженнях, а також в селекції жита. Кариотип ржи посевной (Secale cereale) рассматривается в качестве одного из самых сложных растительных геномов, хромосомы которого трудно различить ввиду одинакового размера. Цель. Выявление вариабельных участков хромосом с помощью повторяющихся последовательностей ДНК в качестве зондов и определение возможности сортинга хромосом у сортов ржи. Методы. Проточная цитометрия и кариотипирование, сортинг хромосом, флуоресцентная гибридизация in situ и микроскопия. Результаты. Различное распределение повторяющихся последовательностей ДНК продемонстрировано у двух сортов ржи и показана возможность сортинга хромосомы 1 у ржи ‘Життедайне’. Это второй случай, когда хромосома 1R была сортирована методом проточной цитометрии у ржи S. cereale. Выводы. Настоящее исследование выявило хромосомный полиморфизм микросателлитной последовательности GAA у сортов ржи и потенциальную возможность сортинга хромосом у Secale и показало возможность использования микросателлитов и классических сателлитов для дальнейших исследований, а также в селекции ржи.